Health, education and the household: Explaining poverty webs - Stella A. Quimbo; Aleli D. Kraft; Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2008)
In this paper, we examine the theory and evidence on the various linkages between poverty, health and education. We introduce the idea of poverty webs to highlight both the cycles and intricate pathways from adverse health and education conditions to poverty and back, within and across generations. The specific pathways considered are (i) labor productivity, (ii) quantity and quality of human capital investments, particularly health and education, and (iii) complementarities between human capital investments. These pathways are analyzed in the context of the household where the adult members typically decide on the critical human capital investments for the young members. Based on previous studies and data from the Philippines and other developing countries, we report evidence on the number of numerous ways by which health, education and poverty are correlated, whether these are intra- or inter-generational effects. Additional evidence of intergeneration transmission is presented using data from the Quality Improvement Demonstration Study (QIDS) on children under 5 years old residing in the central regions of the Philippines. Several policy implications are drawn, with emphasis placed on demand-side interventions that exploit the complementarities of health and education investments.
Keywords: 330; Gesundheit; Arbeitsproduktivität; Bildungsinvestition; Philippinen